2000
DOI: 10.1038/sj.leu.2401677
|View full text |Cite
|
Sign up to set email alerts
|

Antisense therapeutics in chronic myeloid leukaemia: the promise, the progress and the problems

Abstract: DNA sequences which are complementary or 'antisense' to a target mRNA can inhibit expression of that mRNA's protein product. Antisense therapeutics has therefore received attention for inhibiting oncogenes in haematological malignancy, in particular in chronic myeloid leukaemia. However, it is now becoming clear that antisense therapeutics is considerably more problematic than was naively initially assumed. In this article, some of these difficulties are discussed, together with the achievements in CML so far.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 117 publications
0
23
0
Order By: Relevance
“…Theoretically, it is one of the ideal therapeutic agents of CML [9,16] . However, they are very poorly soluble, exhibit low affinity for their target complementary RNA sequences, and target RNase-H poorly.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, it is one of the ideal therapeutic agents of CML [9,16] . However, they are very poorly soluble, exhibit low affinity for their target complementary RNA sequences, and target RNase-H poorly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, probes spanning this region should be avoided. 12,27 In the past decade, antisense oligonucleotides 15,28,29 and…”
Section: Discussionmentioning
confidence: 99%
“…However, since the alteration is located close to the fusion region it may have a significant influence on the annealing of PCR primers, probes for real time PCR 5,[9][10][11][12][13] and therapeutic antisense oligonucleotides. 14,15 Currently, the frequency of this polymorphism and therefore the potential impact is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that the inhibition was sequence dependent but not sequence specific (Mahon et al, 1995;O'Brien et al, 1994). Other investigators reported that inhibition of CML cell proliferation by AS-ODNs is sequence specific but nonantisense mediated (Clark, 2000;Vaerman et al, 1995Vaerman et al, , 1997.…”
Section: Antisense Strategiesmentioning
confidence: 99%
“…Although BCR/ABL may in theory be the most attractive target for antisense therapy, the long half life of P210 BCR/ABL (more than 24 h) poses a significant obstacle (Clark, 2000;Spiller et al, 1998a,b). Prolonged ex vivo culture would therefore be needed to induce cell death in most leukemic cells, which may interfere with engraftment ability of hematopoietic progenitors.…”
Section: Antisense Strategiesmentioning
confidence: 99%